Dynamic regulation of auxin response during rice development revealed by newly established hormone biosensor markers - Yang, Jing; Yuan, Zheng; Meng, Qingcai; Huang, Guoqiang; Périn, Christophe; Bureau, Charlotte; Meunier, Anne-Cécile; Ingouff, Mathieu; Bennett, Malcolm J.; Liang, Wanqi; Zhang, Dabing (Frontiers Media, 2017)
The hormone auxin is critical for many plant developmental processes. Unlike the model eudicot plant Arabidopsis (Arabidopsis thaliana), auxin distribution and signaling in rice tissues has not been systematically investigated due to the absence of suitable auxin response reporters. In this study we observed the conservation of auxin signalling components between Arabidopsis and model monocot crop rice (Oryza sativa), and generated complementary types of auxin biosensor constructs, one derived from the Aux/IAA-based biosensor DII-VENUS but constitutively driven by maize ubiquitin-1 promoter, and the other termed DR5-VENUS in which a synthetic auxin-responsive promoter (DR5rev) was used to drive expression of the yellow fluorescent protein (YFP). Using the obtained transgenic lines, we observed that during the vegetative development, accumulation of DR5-VENUS signal was at young and mature leaves, tiller buds and stem base. Notably, abundant DR5-VENUS signals were observed in the cytoplasm of cortex cells surrounding lateral root primordia (LRP) in rice. In addition, auxinmaxima and dynamic re-localization were seen at the initiation sites of inflorescence and spikelet primordia including branch meristems (BMs), female and male organs. The comparison of these observations among Arabidopsis, rice and maize suggests the unique role of auxin in regulating rice lateral root emergence and reproduction. Moreover, protein localization of auxin transporters PIN1 homologs and GFP tagged OsAUX1 overlapped with DR5-VENUS during spikelet development, helping validate these auxin response reporters are reliable markers in rice. This work firstly reveals the direct correspondence between auxin distribution and rice reproductive and root development at tissue and cellular level, and provides high-resolution auxin tools to probe fundamental developmental processes in rice and to establish links between auxin, development and agronomical traits like yield or root architecture.